IDEOLOGI T-SHIRT BEBASKAN JRX SEBAGAI SEBUAH KOMODITI DAN SIMBOL PERLAWANAN TERHADAP KEKUASAAN - Made Ika Kusuma Dewi; Ida Ayu Dwita Krisna Ari; Widya Duta (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
Clothing has become an important part of the lifestyle and hasbecome a fashion trend in Balinese society. Clothing is very closely relatedto the human self, through clothing can reveal many things about theidentity of the wearer from the appearance reflected how the social statusand personality of the wearer. Currently, the t-shirt is a popular clothingused by people from all walks of life because it is easy to clean and themodel remains eternal from time to time. T-shirts have severalconveniences, apart from being cheap, comfortable to wear, easy to clean,mobile, functional, and can be used as souvenirs, and so on, this makesbusiness people and politicians realize that t-shirts can be used as a gift. aneffective and efficient promotional media, apart from being a means ofadvertising t-shirts, it is also used as a medium to spread politicalunderstanding. Of the several functions possessed by the t-shirt, it isrelated to the function of the t-shirt as a medium for delivering messagesand aspirations. Currently, several types of t-shirts have emerged thatcarry the aspirations of several groups of people who empathize with thecase that befell the drummer for the Superman Is Dead band, I Gede AriAstina, or who is familiarly called Jerink, later shortened to JRX. Regardingthis case, many JRX sympathizers thought that he did not deserve to bepunished, without holding mediation to bridge the problem between JRXand IDI Bali which he criticized, but the JRX case went straight to the legalprocess so that it was considered by some groups of society as an act.silence the aspirations of the small people who try to voice injustice in thiscountry, therefore several individual formation practices have emergedthat determine their common social orientation, this communitymovement group has the same ideology and so that they can actstructurally so that it is in line with their ideology. stretcher, then in theprocess of marking the ideology, several t-shirt designs emerged with thetheme “free JRX” with various variants, designs, colors that emerged fromseveral groups that had the same ideology.